Integrated modelling to assess N pollution swapping in slurry amended soils - Cameira, Maria (2021)
In the present work, it was hypothesized that through modelling it is possible to overcome the constraints that arise in the quantification of N pollution swapping associated to slurry application practiceswhen using individual experimental data. For this, environmental N losses were assessed under two methods of dairy slurry application to a double cropping system (rainfed oats (Avena strigosa)/irrigated maize (Zea mays)) in two different soils. An integrated experimentation and modelling approach was applied using the RZWQM2 model. The modelwas first tested using four years of experimental data concerningN fluxes to/fromdifferent environmental compartments (soilmineralization, N gas emissions, and N leaching). Themodel estimated emissionswith overall efficiencies of ~70% and r2 ~ 0.75. Total N losses were higher for surface band application (95.4 and 40.2 kg ha−1 for the sandy and sandy loam soils, respectively). However, when slurry was injected, nitrate leaching considerably increased (by 107 and 64% for the sandy and sandy loam soils, respectively), even though gas emissions were minimized. This N swapping among path losses requires targeting of the N mitigation measures to the environmental compartment showing the highest vulnerability. Generally, the estimated emission factors (EFs) were lower than or equal to (slurry injection in the sandy loam soil) the IPCC default. The values showed high variability, reinforcing the need to use agricultural system specific EFs. The methodologies used in this study, focused on scenario analysis, can support policy as they can be used to set up integral strategies to decrease N emissions fromlivestock farming systems, taking into account possible synergies and antagonisms produced by the measures among NH3 and N2O emissions and NO3 − leaching